Strategi Pembelajaran Bahasa Inggris Untuk Meningkatkan Skor TOEIC Mahasiswa Politeknik Darussalam - Muhammad Bambang Purwanto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The purpose of this research is to find out the students' strategies in learning English. This research is a descriptive study with a qualitative approach and was carried out at the Darussalam Polytechnic Travel Business Study Program for the academic year 2021/2022. The study involved 40 business travel students in the first and fourth semesters with a TOEIC prediction score of 400 as subjects in this study. To measure students' use of English learning strategies, researchers used the Strategy Inventory of Language Learning (SILL) version 7.0, which was designed by Oxford. The results of this study reveal that the language learning strategies used by students are memory strategies and cognitive strategies with an average of 3.84 and 3.81 which are included in the high category, which is often used. Compensation strategies, metacognitive strategies, affective strategies and social strategies are in the moderate category, which is sometimes used.